Computerization and its Impact on Polytechnic Education - Singla, P. K. (Journal of Engineering Education Transformations, 2000)
Industries, world over, are facing a number of challenges, in terms of production efficiency and quality parameters, due to globalization and competitiveness. The problems are more complicated today because many changes are occurring not only simultaneously but also more rapidly than in the past. These changes are occurring in all sectors of industries whether these are manufacturing, service or agriculture/mining sector industries. Applications of CAD/ CAM/CNC/AUTO CAD and other Computer Integrated Manufacturing (CIM) techniques have come to stay in the Indian industrial scenario. Despite the benefits which automation and computerization can bring, the decisions for investment in ':Advanced Manufacturing Services" mainly depend on the specialized technical/skilled personnel required for manning these enterprises. Technician Engineers being the backbone of any industry, are mainly responsible for executing and managing all types of activities starting right from raw material, processing, marketing, managing and controlling at shop floor, have therefore to be equipped with CIM techniques if they have to sustain in the industry. It is here that role of polytechnic level institutions comes into play to produce matching manpower as per the requirements/ developments of the world of work. Though efforts have been made by Curriculum Development Centres (CDCs) of Technical Teachers' Training Institutes and states in different regions of the country to include these CIM techniques in various engineering/vocational/art base curricula, there exists a large gap between curricula and its implementation. In order to fill-up this gap it is absolutely necessary to i) provide training and develop competency in each teaches; working in the polytechnic, to handle various computer softwares available for designing, drafting, testing, processing, managing etc., irrespective of the courses/subjects the teacher is handling ii) develop/procure various engineering/vocational/art application computer software packages iii) develop infrastructure and environment to ensure use of CAUCAI and other multimedia for better comprehension, understanding and skill development in the students. An integrated approach is essential to bridge the gaps between industry, curriculum and polytechnics.